The Role of the Regional Inspectorate of Supervision in Strengthening Transparent and Accountable Police Governance at the North Sumatra Regional Police - Amalia, Yunda; Aspan, Henry; Siregar, Mhd. Azhali (International Conference Epicentrum of Economic Global Framework, 2026)
The reform of the Indonesian National Police toward a Professional, Modern, and Trustworthy institution positions internal oversight as the backbone of transparent and accountable governance. The Regional Inspectorate of Supervision (Itwasda) functions as the internal oversight unit at the Regional Police level, yet its effectiveness is frequently questioned because it is embedded within the very structure it is meant to control. This study aims to analyse the role and legal standing of Itwasda in strengthening transparent and accountable police governance within the North Sumatra Regional Police, and to identify the obstacles together with the formulation for its reinforcement. The research employs a normative legal method complemented by an empirical approach, applying statute, conceptual, and case approaches, with legal materials analysed qualitatively and prescriptively. The findings reveal that Itwasda plays a strategic role through audit, review, evaluation, monitoring, and routine inspection that sustain the principles of accountability and openness, although its optimisation is hampered by limited structural independence, sectoral egoism, corps culture, weak follow-up of recommendations, and a shortage of certified auditors. The study recommends strengthening functional independence, synergy with external oversight bodies, digitalising supervision, and cultural reform so that the function of Itwasda evolves from administrative formality into a tangible instrument of public accountability.